(untitled) (EU and comparative law issues and challenges series (ECLIC), 2024)
The EU invests immense resources to promote human rights in a number of societies outside of its borders. Notably, the European Neighbourhood Policy and Enlargement focus on societies right next to the EU and with the potential to become an EU member states. In this chapter, we will focus on the cost of human rights in post-conflict societies, with a focus on the Western Balkans and Kosovo. If we understand the case of Kosovo, we will be better prepared to understand the costs the EU is ready to invest in countries such as Ukraine or any other country in its neighbourhood. The non-recognition of Kosovo by the UN and the EU places it in a very interesting legal and political disambiguation that makes the assistance of the EU vital. The EU-run EULEX mission in Kosovo, its mandate, costs and also corruption scandals put an additional burden and cost on its work. The future success and integrity of the EU run Kosovo Specialist Chambers, which should finalise the justice efforts in Kosovo are at stake due to a declining support for EULEX from both the Kosovo Serbs and Albanians. The corruption allegations of EULEX put in danger the future work of the Kosovo Specialist Chambers and the costs the EU bears. If EULEX fails it will come at a very high cost for the EU and even the already very low level of human and minority rights in Kosovo could not be further guaranteed. The final implementation of informal agreements regarding Kosovo in the form of The Brussels Agreement from 2013 and The Washington Agreement from 2020 having only a partial implementation success is a challenge for the rule of law in Kosovo. The future of post-conflict development is gaining a new shape and its formation is something we are able to witness and follow in Kosovo, through the lenses through which the EU supports is coming with all its various challenges and possible shortcomings.